Secret Sharing Schemes Based on Extension Fields (European Journal of Pure and Applied Mathematics, 2018)
A (t, n)âˆ’secret sharing scheme is a method of distribution of information among n participants such that t > 1 can reconstruct the secret but t âˆ’ 1 cannot. There is numerous research about secret sharing schemes. However there is little research on secret sharing schemes based on extension fields. In this paper, we study secret sharing schemes based on extension fields over finite fields. We use two methods to recover the secret. We define the access structure and the accessibility degree for these secret sharing schemes. We also describe our theorems, definitions and a corollary